2020
DOI: 10.3389/fpsyt.2020.570164
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms and Behavioral Changes in Children and Adolescents During the Early Phase of COVID-19 Quarantine in Three European Countries

Abstract: The coronavirus disease (COVID-19) pandemic forced the home confinement of the majority of population around the world, including a significant number of children and adolescents, for several weeks in 2020. Negative psychological effects have been identified in adults, but research about the impact of this type of social distancing measure on children and adolescents is scarce. The present study aimed to describe and compare the immediate psychological and behavioral symptoms associated with COVID-19 quarantin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
196
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(234 citation statements)
references
References 41 publications
28
196
4
6
Order By: Relevance
“…This situation can be explained by the anxiety, fears of the virus and the stress period that the children and families face. Stress-related sleep problems are common and particularly during the quarantine period [ 18 , 19 , 33 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation can be explained by the anxiety, fears of the virus and the stress period that the children and families face. Stress-related sleep problems are common and particularly during the quarantine period [ 18 , 19 , 33 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies suggest that the effects may be troublesome [ 18 ]. Recent studies found that, compared to pandemic quarantines, being more structured, class days give children more opportunities to be physically active, spend less time in front of screens, and regulate their sleep schedules [ 7 , 19 ]. Additionally, pandemic stressors such as being in isolations, one of the family members infection of Coronavirus, frustration and boredom may have even more negative impacts on children’s behavior and emotions [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later, in 2019, Canals et al found a prevalence of any anxiety disorder of 11.8%, with high rates of comorbidity with depression and other anxiety disorders, low use of professional support (33.3%), and high persistence of diagnosis in a 2-year follow-up (52.9%). More recently, the increase of psychological and behavioral changes, especially emotional symptoms, in Spanish children and adolescents during the early phase of COVID-19 quarantine has been reported (Francisco et al, 2020 ). Also, this presence of emotional symptoms, among others, at subclinical level raise the risk of subsequent development of mental disorder (Fonseca-Pedrero et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that older children have a steeper decrease in other fundamental activities when participating in screen activities, such as outdoors and free playtime activities. Some studies revealed that children suffered significant changes in their daily habits during the confinement period, spending more than 3 h using screens and halving the time spent in physical activities (Francisco et al, 2020;Morgül et al, 2020).…”
Section: Resultsmentioning
confidence: 99%